Polynomial convexity properties of closure of domains biholomorphic to balls - JOIȚA, Cezar (Studia Universitatis Babeș-Bolyai Mathematica, 2022)
We discuss the connections between the polynomial convexity proper- ties of a domain biholomorphic to ball and its closure. Mathematics Subject Classification (2010): 32H02, 32E15. Received 10 January 2022; Accepted 18 January 2022.